TAUHID-BASED SELF-HEALING AS AN EFFORT TO OVERCOME NON-SUICIDAL SELF-INJURY: A STUDY ON THE STORY OF PROPHET YUSUF IN THE QUR'AN - Lasmana, Nunung; Winata, Muhammad Yanuar (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2024)
Every individual inevitably encounters pressures, conflicts, and social relationship challenges throughout their lives. While some individuals are able to navigate these difficulties successfully, others may struggle, leading to prolonged mental stress. In severe cases, this can manifest in self-harming behaviors, including Non-Suicidal Self-Injury (NSSI). To prevent such behaviors, effective self-healing strategies are essential. For Muslims, one source of inspiration for self-healing is the tauhid-based approach exemplified by Prophet Yusuf, who endured significant trials from his brothers and his environment. This study explores the concept of tauhid-based self-healing as demonstrated by Prophet Yusuf to understand how he managed to avoid prolonged mental stress. Employing a descriptive-analytical method, the study examines the narrative of Prophet Yusuf, highlighting his adversities—such as being thrown into a well, falsely accused of theft, and slandered with adultery—and his strategies to overcome them. The findings reveal that Prophet Yusuf employed tauhid-based self-healing through self-compassion, compensation, mindfulness, and open-mindedness, providing valuable insights into addressing NSSI.